2021
DOI: 10.1002/adfm.202107567
|View full text |Cite
|
Sign up to set email alerts
|

All‐Green Solvent‐Processed Planar Heterojunction Organic Solar Cells with Outstanding Power Conversion Efficiency of 16%

Abstract: Device engineering is an effective way to improve the photovoltaic performance of organic solar cells (OSCs). Currently, the widely used bulk heterojunction (BHJ) structure has problems such as material solubility limitations and the emerging pseudoplanar heterojunction (PPHJ) structure is also troubled by printing technology requirements. However, these issues can be solved by the reasonable application of traditional planar heterojunction (PHJ) structure. Herein, PM6:BO‐4F system is selected to prepare PHJ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 44 publications
0
56
0
Order By: Relevance
“…Such a structure was defined previously as a quasiplanar heterojunction (Q-PHJ). [32][33][34][35] In the Q-PHJ structure, each component of the bilayer can be separately optimized, which facilitates better control of the active layer morphology and targeted analysis. This kind of structure achieves efficient exciton dissociation without adversely affecting the transports of the carriers in either the polymer donor or acceptor layers, and the carrier recombination could be reduced significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Such a structure was defined previously as a quasiplanar heterojunction (Q-PHJ). [32][33][34][35] In the Q-PHJ structure, each component of the bilayer can be separately optimized, which facilitates better control of the active layer morphology and targeted analysis. This kind of structure achieves efficient exciton dissociation without adversely affecting the transports of the carriers in either the polymer donor or acceptor layers, and the carrier recombination could be reduced significantly.…”
Section: Introductionmentioning
confidence: 99%
“…After two pioneering works were reported, much effort has been made on optimizing processing solvents by several research groups. [30,32,33,[36][37][38][39]47,57,60,62] Yan et al demonstrated the importance of the chemical structures of the underlying polymer layer by using various processing solvents including CF, THF, toluene, chlorobenzene (CB), and ortho-xylene (o-XY). [34] The major limitation in the fabrication of LbL OSCs is the restriction in solvent selection for processing an NFA top layer; the underlying polymer film can be destroyed if NFAs are processed with nonorthogonal or highboiling-point solvents.…”
Section: Importance Of Solvent Choice For Desired Lbl Morphologymentioning
confidence: 99%
“…After two pioneering works were reported, much effort has been made on optimizing processing solvents by several research groups. [ 30,32,33,36–39,47,57,60,62 ]…”
Section: Vertical P–i–n Morphology Controlmentioning
confidence: 99%
“…The environmental impact of solution processed OSCs can be mitigated by introducing halogen-free solvents or green solvents during the fabrication processes. [33][34][35][36][37] Potential bottlenecks to low-cost OSC production lie largely in the cost of raw materials, especially for active layer materials. 38,39 Therefore, it is important to develop low-cost and efficient acceptor materials.…”
Section: Msde Reviewmentioning
confidence: 99%